Elizabeth Blackwell : first woman physician - Binns, Tristan Boyer, 1968- (New York : Franklin Watts, 2005)
Presents a short biography of Elizabeth Blackwell, who in 1849 became the first women to earn a medical degree in the United States and discusses the challenges she faces and her efforts to provide better health care to women and children.
A bright beginning -- A hard challenge -- Gaining experience -- Struggling to start -- New beginnings -- Challenges and successes -- War and opportunity -- Starting over -- London triumph -- Active until the end.
Includes bibliographical references (p. [103]) and index.
5.6
5-8
Keywords: Blackwell, Elizabeth, -- 1821-1910 -- Juvenile literature; Women physicians -- United States -- Biography -- Juvenile literature; Women physicians -- England -- Biography -- Juvenile literature; Blackwell, Elizabeth, -- 1821-1910.; Women physicians; Blackwell, Elizabeth, -- 1821-1910.; Women physicians -- Biography